Desempenho silvicultural de espécies florestais introduzidas para sistema silvipastoril em Lavras, MG - Nieri, Erick Martins (2016)
The increase in the demand for wood and food products establishes the need to turn unproductive areas into productive lands. Therefore, the establishment of silvopastoral systems emerges as an alternative for the recovery of degraded pastures. The objective of this research was to evaluate the silvicultural performance of seven introduced forest species in different arrangements of silvopastoral systems implanted in a degraded pasture in Lavras, MG. The experiment was established in January 2012 in the experimental farm of the Agricultural Research Corporation of Minas Gerais (EPAMIG), unit Lavras/ MG, which is located in the transition area between Cerrado and Atlantic Forest. The planted species were Toona ciliata M. Roemer (Australian Red Cedar), sexually and vegetatively propagated, Calophyllum brasiliense Cambess (guanandi), Khaya senegalensis A. Juss (African mahogany), Tectona grandis L. F (teak), Acacia mangium Willd (black wattle), Dipteryx alata Vogel (baru) and hybrid of Eucalyptus urophylla x Eucalyptus grandis (Eucalyptus 1528). In order to evaluate the establishment potential of Australian Red Cedar, African mahogany, teak and guanandi, a randomized block design in a split plot by time with four repetitions was used. The plots consisted of one structural arrangement of (3(3x2) + 7x2) m. The subplots were composed of five growth assessment times of the species (12, 18, 31, 36 and 43 months after planting). The black wattle, baru and eucalyptus 1528 were evaluated in strips, with species such as plots and spacing as sub-plots. The experiment was established in a randomized block design with four repetitions and evaluated at different times, where the time factor corresponds to the effect of sub-plot. The subplots consisted of 3x2m e 7x2m spacings. The subplots contained five periods of performance assessment (12, 18, 31, 36 and 43 months). It was concluded that the cloned Australian Red Cedar performed better under the arrangement studied within the silvopastoral system for the recovery of degraded pasture, and among the studied species, guanandi showed both the lowest silvicultural performance and symptoms of poor adaptation to the site. Regarding acacia, eucalyptus 1528 and baru, these species had adapted to soil and climatic conditions of the region. However, the eucalyptus 1528 was the species that obtained the highest growth rate over time. Among the tested spacings, the 7x2m spacing promoted better performance for the region. The growth in diameter at breast height was higher in 7x2m spacing for all species, evidencing that higher useful area promotes greater secondary growth.